2005
DOI: 10.1007/s11064-005-8825-9
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and Zinc Modulate Outgrowth from Goldfish Retinal Explants

Abstract: Taurine and zinc, highly concentrated in the retina, possess similar properties in this structure, such as neuro-protection, membrane stabilization, influencing regeneration, and modulating development, maybe by acting in parallel or as interacting agents. We previously demonstrated that there are some correlations between taurine and zinc levels in hippocampus, dentate gyrus and retina of the developing rat. In the present study we evaluate the possible effects of taurine and zinc on outgrowth from goldfish r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…The trophic effect of taurine is inhibited by µM concentrations of zinc in cultures of goldfish retinal explants [16]. In addition, taurine does not counteract the inhibitory effect of 1 µM zinc [16], which may be due to inhibition of taurine transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trophic effect of taurine is inhibited by µM concentrations of zinc in cultures of goldfish retinal explants [16]. In addition, taurine does not counteract the inhibitory effect of 1 µM zinc [16], which may be due to inhibition of taurine transport.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effect of low concentrations of zinc in the brain has been attributed to its antioxidant function and to the fact that zinc is an important modulator of excitatory synaptic transmission [7,15]. Zinc occurrence in cultures of goldfish retinal fragments at a concentration equal to or greater than 0.06 µM in the presence of taurine reduces the amino acid trophic effect, which could be related to the interaction between both in the membranes or to the influence of zinc on taurine transport [16]. It has been demonstrated that micromolar concentrations of zinc modulate the activity of voltage-dependent calcium channels, of receptors and of neurotransmitter transporters [17-20].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, porcine retinal explants are mostly used to analyze neuroprotection and cell survival, rather than neurite outgrowth MartinezFernandez;de la Camara et al 2014;Taylor et al 2014;Bell et al 2016). Regarding anamniote models, retinal explants harvested from goldfish or zebrafish have also been used to test the putative effect of both intrinsic and extrinsic factors on RGC outgrowth/regeneration, albeit to a more limited extend (Nusetti et al 2005;Veldman et al 2007Veldman et al , 2010Cubillan et al 2012;Ou et al 2012;Ogai et al 2014). To culture fish retinal explants, retinas are chopped into small squares and transferred to poly-L-lysine-coated well plates.…”
Section: Ex Vivo Tissue Explant Studies In Other Vertebratesmentioning
confidence: 99%
“…Measurement of taurine concentrations was accomplished by using the HPLC method described by McMahon et al [22]. Tissue homogenate preparation was made according to Nusetti et al [24]. In brief, 100 mg whole brain sample was homogenized in 0.1 N perchloric acid and centrifuged for 10 min at 6.000 g and 4°C.…”
Section: Hplc Analysismentioning
confidence: 99%